Evaluation of Semicircular Canal Function by Video Head Impulse Test in Patients With Facial Nerve Schwannoma. Issue 5 (June 2020) - Fujiwara, Keishi; Morita, Shinya; Furuta, Yasushi; Yanagi, Hiroko; Hoshino, Kimiko; Fukuda, Atsushi; Nakamaru, Yuji; Homma, Akihiro
Abstract : Objectives: The aim of the present study was to evaluate semicircular canal function by video Head Impulse Test (vHIT) in patients with facial nerve schwannoma (FNS). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Seven patients with FNS underwent vHIT examination. Main Outcome Measures: The gain in vestibulo-ocular reflex and the presence of catch-up saccade were examined for the semicircular canals including the vertical canals. Results: Dysfunction of the semicircular canals was detected by vHIT in three of seven cases. Nystagmus beating toward the non-affected side was observed in all three cases with semicircular canal dysfunction. Dysfunction was observed in a case with no direct compression of the vestibular nerve or semicircular canals by FNS. Conclusions: Semicircular canal function in patients with FNS could be evaluated by vHIT. vHIT has two advantages for the evaluation of vestibular function in patients with FNS. First, vHIT could be used for the patients in whom a tumor exists in the external auditory canal or middle ear, unlike caloric testing. Second, as vHIT could evaluate all three canals, impaired vestibular nerves could be speculated from vHIT results when a tumor exists in internal auditory canal. vHIT should be performed in patients with FNS, especially before surgery, to evaluate vestibular function.